CONSTRUCTION SELF-PROPELLED PNEUMOPUNCHERS WITH LOCKING MECHANISM - V. K. Perederey (Наука и техника)
The paper reveals one of possible methods for higher productivity and reliability of building self-propelled pneumopunchers which are intended for making holes in soil while using trenchless method and constructing various engineering communications under car, tram and rail lines, airport runways. A new design of building pneumopuncher with increased productivity due to higher speed for hole formation in soil and its reliability has been presented in the paper. A formula for determination of displacement increment for a new pneumopuncher in comparison with the conventional one has been obtained in the paper. The paper describes a design and operation principal of the building self-propelled pneumopuncher which is equipped with a locking mechanism with the purpose to neutralize action of soil elastic forces and reactive repulsive force. The locking mechanism keeps the pneumopuncher in the hole. The pneumopuncher consists of a body with anvil, movable hammer, a manifold which is set in axial deepening of the hammer, a nut and a locking mechanism. Improvement of operational pneumopuncher reliability is attained due to the fact that the locking mechanism is made in the form of two coaxially positioned inner and outer cups having a common basis. A piston is installed in the middle of the inner cup, a spring is fixed over the piston and a rod with a breaking shoe is positioned at the end. Height of the inner cup is less the outer cup height and there is an annular cavity between them which is connected with a chamber. The chamber is formed by the piston, the inner cup and the manifold. The annular cavity through an opening in the inner cup wall, two sylphons, a channel in the nut end and an opening in the vertical wall of the manifold are connected with a chamber of operating stroke. The sylphons are placed between the outer cup and the nut, between the nut and the manifold. Differential equations for movement of pneumopuncher in soil have been compiled. While solving the equations a formula for determination of increase in displacement of the pneumopuncher with the locking mechanism and without it has been obtained in the paper.